Mason Brayman, Revised Statutes of the State of Illinois: Adopted by the General Assembly of Said State, at Its Regular Session, Held in the Years A.D. 1844-45: Together with an Appendix Containing Acts Passed at the Same and Previous Sessions, Not Incorporated in the Revised Statutes, but Which Remain in Force , at 176 (1845), Criminal Jurisprudence, § 139 - (:unkn) unknown (General Publisher, 1845)
Prohibited the carrying of “any pistol, gun, knife, dirk, bludgeon or other offensive weapon, with intent to assault any person. Punishable by fine up to $100 or imprisonment up to 3 months.
--
Keywords: CARRY - INTENT TO COMMIT CRIME